New requirements for modern education in colleges and professional schools in the context of the introduction of modern information and telecommunication technologies - K T Aldiyarov (RUDN Journal of Informatization in Education, 2012)
Informatization of the society, the gradual establishment in Kazakhstan information society brings new demands to the quality of graduates of professional schools and colleges